Hubungan Kompetensi Kepribadian Tutor Dengan Hasil Belajar Peserta Didik Mata Pelajaran IPA Paket C di Pusat Kegiatan Belajar Masyarakat Sentosa Hati Kota Padang - Kelvin Pratama Putra; Solfema Solfema (Universitas Negeri Padang, 2023)
The background of this research is the low learning outcomes of students in Package C in the Biology subject at the Sentosa Hati Community Learning Activity Center, Padang City. The objectives in this study are (1). to describe the personality competence of the tutor, (2). to describe the results of studying biology, (3). to see the relationship between tutor personality competencies and learning outcomes of biology students in package c at the Sentosa Hati Community Learning Activity Center. This research is a research with a quantitative approach and correlational type. The population of this study were students in biology subjects at the Sentosa Hati Community Learning Activity Center. The sample collection technique uses Random Sampling. The data collection technique was in the form of a questionnaire with a conducive data collection tool, significant biology learning outcomes between tutor personality competencies and student learning outcomes in biology subject in package c at the Sentosa Hati Community Learning Activity Center, Padang City. The results showed that the personality competence of tutors in Package C was low, and the learning outcomes of biology students were still low, and there was a significant relationship between tutor personality competencies and biology learning outcomes in package c at the Sentosa Hati Community Learning Activity Center, Padang City. Where for tutors to be able to develop personality competencies in the biology learning process in order to achieve increased student learning outcomes.